Evaluasi Dampak Keterbatasan Alat Praktik Fiber Optik Terhadap Capaian Pembelajaran Mata Pelajaran Teknologi Jaringan Kabel dan Nirkabel pada Implementasi Kurikulum Merdeka di Program Keahlian Teknik Jaringan Komputer dan Telekomunikasi - Sovandi Marwan; Ambiyar Ambiyar; Hasan Maksum (Education Achievement: Journal of Science and Research, 2026)
The rapid development of digital technology in the era of Industry 4.0 and Society 5.0 has increased the demand for skilled human resources, particularly in information technology and telecommunications. One of the essential competencies required by industry is the ability to install, test, maintain, and troubleshoot fiber optic networks. However, many vocational high schools (SMKs) face limitations in the availability of fiber optic practice equipment, which may affect students’ learning achievement. This study aimed to evaluate the impact of limited fiber optic practice equipment on learning outcomes in the Technology of Wired and Wireless Networks (TJKN) subject within the implementation of the Merdeka Curriculum in the Computer and Telecommunications Network Engineering (TJKT) program. The study employed the Context, Input, Process, Product (CIPP) evaluation model with a mixed-methods approach using a convergent design. Data were collected through observations, questionnaires, interviews, and document analysis involving 72 Grade XI TJKT students, teachers, the head of the study program, and laboratory personnel. The findings revealed that the Context component achieved the highest score (84.13%), indicating that the learning objectives and competencies were highly relevant to industry needs. Meanwhile, the Input component obtained the lowest score (62.45%) due to the limited availability of key equipment such as fusion splicers, OTDRs, and optical power meters. The Process component reached 76.85%, while the Product component scored 71.33%. Furthermore, a strong positive correlation (r = 0.67) was found between practice intensity and students’ skill achievement. The study concludes that although the learning program has been implemented effectively, inadequate practical facilities remain a major challenge affecting the quality of hands-on learning experiences and the achievement of technical competencies. Therefore, strengthening laboratory facilities and industry partnerships is essential to improve vocational education quality and graduate employability.